Some remarks on the Roman religious architecture: the building of temples according to ‘De architectura’ by Vitruvius - Gonçalves, Ana Teresa Marques; Cunha, Macsuelber de Cássio Barros da (Romanitas - Revista de Estudos Grecolatinos, 2015)
The only Roman treatise on architecture, which reached our days almost complete, the De architectura by Vitruvius, holds a great importance for the study of the Roman architecture. Written and published at the time of transition between the Republic as a form of government, and what became known as the Principate, this work has a strong connection with the context to which it belongs being clearly connected to the building policy of Octavian Augustus, to whom the work is dedicated. In this work, we use the De architectura to reflect on the main Vitruvius’ guidelines about the construction of temples, the house of the gods.
Keywords: Early Roman Empire; De architectura; Religious architecture; Temples